Two-decade spatiotemporal variations in ground-level ozone over Ontario, Canada - Zang, Zhou; Liu, Jane; Ge, Erjia; Zhang, Yi (Frontiers in Environmental Engineering, 2025)
IntroductionGround-level ozone (O3) remains a persistent air quality concern in Ontario, Canada’s most populous province. Understanding long-term trends and spatially explicit details of O3 is important for supporting air quality management in Ontario.MethodWe construct a high-resolution (daily, 10 km) dataset of maximum daily 8-hour average O3 (MDA8 O3) over Ontario from 2004 to 2023, through a two-step machine learning model. The model has incorporated our hypothesis that accounting for transboundary influences can enhance the accuracy of O3 estimation.ResultsValidation against in-situ measurements confirms the hypothesized high accuracy of the dataset (R2 = 0.82, RMSE = 4.99 ppb), outperforming the traditional model and two existing datasets. The dataset reveals pronounced spatiotemporal heterogeneity in MDA8 O3 concentrations, which are low in northern Ontario but high in southern Ontario, especially in southwest Ontario. Seasonally, the provincial mean MDA8 O3 peaks in spring (∼40 ppb) and dips in autumn (∼27 ppb), while spatial MDA8 O3 in summer is most heterogeneous among all seasons, with a peak in southwestern Ontario. From 2004 to 2023, the provincial mean MDA8 O3 shows no significant trend, while a significant decreasing trend (−0.1 ppb/year, p < 0.05) appears in southern Ontario, where MDA8 O3 increases in winter but decreases in summer, both significantly. The number of days exceeding the World Health Organization (WHO) O3 guideline range from 10 to 80 days in southern Ontario, with a decline of 1–4 days (up to 15%) per year over 2004–2023.DiscussionThe analysis suggests that O3 in southern Ontario is impacted by both anthropogenic emissions and meteorology. Reductions in O3 precursor emissions have effectively lowered summertime O3 across southern Ontario, partially offsetting the meteorological-driven increase in O3. This MDA8 O3 dataset offers a valuable resource for further research in environmental health, air quality policy, and O3 impact on agriculture.